2013
DOI: 10.1093/carcin/bgt349
|View full text |Cite
|
Sign up to set email alerts
|

Impairing squamous differentiation by Klf4 deletion is sufficient to initiate tongue carcinoma development upon K- Ras activation in mice

Abstract: Oral squamous cell carcinoma (SCC) is among the most prevalent cancers in the world and is characterized by high morbidity and few therapeutic options. Like most cancers, oral SCC arises from a multistep process involving alterations of genes responsible for balancing proliferation and differentiation. Among these, Krϋppel-like factor 4 (Klf4) suppresses cell proliferation and promotes differentiation and thus helps to maintain epithelial homeostasis. However, the prevailing role of Klf4 in maintenance of norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 42 publications
3
38
1
Order By: Relevance
“…Our findings are consistent with the previous finding that Klf4 deletion sufficiently initiated carcinoma development upon K-ras activation in mouse tongue. 35 Multiple mechanisms of KLF4 downregulation in lung cancer. KLF4 mutations were identified in fewer than 2% of the total patients (Figure 1a), suggesting that genetic mutation is not the main cause of KLF4 downregulation in lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with the previous finding that Klf4 deletion sufficiently initiated carcinoma development upon K-ras activation in mouse tongue. 35 Multiple mechanisms of KLF4 downregulation in lung cancer. KLF4 mutations were identified in fewer than 2% of the total patients (Figure 1a), suggesting that genetic mutation is not the main cause of KLF4 downregulation in lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that KLF4 may maintain a tumor-suppressive function in cells of ductal and islet epithelial lineages, whereas overexpression of KLF4 in acinar cells may result in acinar-to-ductal reprogramming, which potentiates the initiation of PanIN in the presence of mutant KRAS . However, Klf4 deletion was found to synergize with mutant KRas to facilitate carcinoma development in mouse tongue and lung (Abrigo et al, 2014). Of note, we also observed accelerated development of skin neoplastic lesions in PRK mice compared with PR mice, and specific Klf4 gene ablation was detected in the skin tumor tissues derived from PRK mice, which is consistent with previous studies showing that Pdx-1 is expressed in skin epidermal cells (Mazur et al, 2010), and Klf4 deficiency promoted the skin tumorigenesis in a classical DMBA/TPA mouse skin cancer model (Li et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of ZNF750 has been reported to result in impaired differentiation and enhanced proliferation of cancer cells (8). ZNF750 interacts with the terminal epidermal differentiation factor KLF4 to induce the expression of differentiation-associated genes (7), and KLF4 deletion is sufficient to impair squamous cell differentiation and initiate tongue carcinoma development (2). In line with these previous reports, the present study revealed that ZNF750 upregulates the differentiation genes LCE3A and SPRR1a, and increases the expression of KLF4, while reducing the expression of MMP28.…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is associated with a high rate of morbidity and mortality, with few therapeutic options (2). The survival rate for patients with OSCC has not improved in recent decades despite the development of novel therapies (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation